Synthesis and characterization of cellulose acetate produced from recycled newspaper - Rodrigues Filho, Guirnes; Monteiro, Douglas Santos; Meireles, Carla da Silva; Nascimento de Assuncao, Rosana Maria; Cerqueira, Daniel Alves; Barud, Hernane Silva [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messadeq, Younes [UNESP] (Elsevier B.V., 2008)
In this work, the viability of recycling newspaper for producing cellulose acetate was tested. Newspaper recycling is extremely important not only for the environment preservation, but also from the economical point of view of aggregating value to this residue. Cellulose acetate was produced from a homogeneous acetylation, and then characterized by FTIR, DSC and TGA. Acetylation times were 48 h for as received newspaper (CA48) and 24 h for delignified newspaper (CA24), resulting in cellulose diacetate (DS = 1.98 +/- 0.22) for CA48 and cellulose triacetate (DS = 2.79 +/- 0.02) for CA24, respectively. Membranes of these materials were produced and characterized according to the previously mentioned techniques and by measurements of water vapor flux, which were compared to membranes of nanofiltration SG from Osmonix (R). Results showed that independently of a purification step, it is possible to produce cellulose acetate membranes through the chemical recycling of newspaper and that membrane CA24 presents thermal stability comparable to membranes produced of commercial cellulose acetate. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: cellulose acetate; newspaper; membranes; recycling